Motivation to succeed is not enough: motivated students need to know how to plan/organize their steps on their way to success - Lisá, Elena; Sokolová, Lenka; Jablonická, Paulína; Kardelisová, Lea (Frontiers in Psychology, 2023)
The study is based on dispositional (career motivation) and social-cognitive (generalized self-efficacy) theories of personality, further on the expectancy-value theory of achievement motivation and future time perspective theory (task value, time, and study environment). The study aimed to explain the mechanism of the prediction relationship between motivation and students’ performance. It was assumed that skills of planning and organizing (operationalized as generalized self-efficacy and learning strategies) mediate the prediction of motivation (career motivation and task value) on students’ success (operationalized as academic achievement and employability). In two studies (N = 313, N = 219), the hypotheses of the mediation models were supported by structural equation modeling. Generally, the skills of organizing/planning fully mediated the students’ performance, measured as academic achievement and employability (number of employers). The results show the importance of combining dispositional motivation characteristics with dynamic planning skills on the way to students’ success. Traditional psychological predictors of performance, like general mental ability and conscientiousness, were not controlled. Higher education institutions could support motivated students on their way to success by teaching them how to plan and organize specific steps on their way to success.